An Analysis of Consumer Behaviors in Choosing Public Transportation - Hadhori Nurhasan; Utomo Sarjono Putro (Journal of Indonesian Applied Economics, 2021)
Various efforts have been done to overcome or at least reduce the severe congestion in Jakarta. For this reason, the local government continues to carry out various strategies. And PT TransJakarta as a company under the auspices of the local government that manages several modes of transportation, also has a big role in overcoming congestion in Jakarta. One of them is by launching several public transportations so that many people will switch to use public transportation. Recently, Transjakarta launched a microbus type public transportation called Mikrotrans. To make it works, TransJakarta must be able to attract public interest to use microtrans. For this reason, a special strategies are needed to attract customers. One of the most important aspects is by controlling the quality of the service in order to make customer satisfied. Several aspects of microtrans service quality are investigated which have major influences on increasing customer satisfaction. And the results show that in general the quality of service at Mikrotrans is quite good. The result shows that the variables of service quality in mikrotrans are good enough in the customer although it still requires evaluation or improvement in several aspects